Ўрта осиё давлат университети (САГУ) олимларининг помирга уюштирилган экспедицияларда иштироки (1923-1928 йиллар) - Кенжаева, Н.С (SCIENCE and SOCIETY, 2020)
The paper deals with the study of the territory of the Pamirs expeditions of the USSR Academy of Sciences in the period 1923-1928, and the participation of scientists from SAGU. The author reviews the principal directions explore the region. It is shown how the prepa- ration of expeditions took place. In addition, the main scientific results and the results of the expeditions were studied.
Keywords: Pamir; expedition; Tajikistan; Academy of Sciences of the USSR; Central Asian State University